2022
DOI: 10.2196/21994
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Care Platform System (C3-Cloud) for Care Planning, Decision Support, and Empowerment of Patients With Multimorbidity: Protocol for a Technology Trial

Abstract: Background There is an increasing need to organize the care around the patient and not the disease, while considering the complex realities of multiple physical and psychosocial conditions, and polypharmacy. Integrated patient-centered care delivery platforms have been developed for both patients and clinicians. These platforms could provide a promising way to achieve a collaborative environment that improves the provision of integrated care for patients via enhanced information and communication t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Other factors that contributed to the choice of the SOP approach are that it was used successfully in ADLIFE’s precursor project, C3-Cloud (von Tottleben et al. , 2022) to ensure that the pilots adopted a standardized approach to running the pilot during the project.…”
Section: Methodsmentioning
confidence: 99%
“…Other factors that contributed to the choice of the SOP approach are that it was used successfully in ADLIFE’s precursor project, C3-Cloud (von Tottleben et al. , 2022) to ensure that the pilots adopted a standardized approach to running the pilot during the project.…”
Section: Methodsmentioning
confidence: 99%
“…Research demonstrated that computerized decision support tailored to the patient successfully improved decision-making [10,11]. Such tools enhanced the decision-making abilities of HCPs in various domains, including effective prescription decisions [12,13], adherence to guidelines for cardiac rehabilitation [14], management of hypertension and diabetes [15][16][17][18][19][20][21], cancer screening [22,23], and computerized order decisions [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the conduction of MDT meetings can be challenged by time restrictions, the unavailability of all members, and increased administrative work [16,17]. The development and uses of new applications have already been tested for daily health decisions [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%